A Phase I Dose Escalation Study Demonstrates Quercetin Safety and Explores Potential for Bioflavonoid Antivirals in Patients with Chronic Hepatitis C. (1st December 2015) - Lu, Nu T.; Crespi, Catherine M.; Liu, Natalie M.; Vu, James Q.; Ahmadieh, Yasaman; Wu, Sheng; Lin, Sherry; McClune, Amy; Durazo, Francisco; Saab, Sammy; Han, Steven; Neiman, David C.; et al.
Abstract : The hepatitis C virus (HCV) infects more than 180 million people worldwide, with long‐term consequences including liver failure and hepatocellular carcinoma. Quercetin bioflavonoids can decrease HCV production in tissue culture, in part through inhibition of heat shock proteins. If quercetin demonstrates safety and antiviral activity in patients, then it could be developed into an inexpensive HCV treatment for third world countries or other affected populations that lack financial means to cover the cost of mainstream antivirals. A phase 1 dose escalation study was performed to evaluate the safety of quercetin in 30 untreated patients with chronic HCV infection and to preliminarily characterize quercetin's potential in suppressing viral load and/or liver injury. Quercetin displayed safety in all trial participants. Additionally, 8 patients showed a "clinically meaningful" 0.41‐log viral load decrease. There was a positive correlation ( r  = 0.41, p  = 0.03) indicating a tendency for HCV decrease in patients with a lower ratio of plasma quercetin relative to dose. No significant changes in aspartate transaminase and alanine transaminase were detected. In conclusion, quercetin exhibited safety (up to 5 g daily) and there was a potential for antiviral activity in some hepatitis C patients. Copyright © 2015 John Wiley & Sons, Ltd.